Anti-ultraviolet silk and preparation method thereof
Through nanocomporation and chemical grafting technology, the combination of modified nanoparticles and phenolic hydroxy conjugates solves the problem of easy shedding inorganic nanoparticles, improves ultraviolet resistance and durability, and is suitable for high-end textile fields.
Patent Information
- Application Number
- CN202510619416.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-08-08
AI Technical Summary
In the prior art, inorganic nanoparticles have weak binding force and are prone to fall off, resulting in undustable UV resistance, and the traditional process is complex or functional to sacrifice fiber softness and breathability.
Using nanocomporation and chemical grafting technology, using modified nano ZnO or TiO2 with phenolic hydroxy conjugates and aldehyde crosslinking agents, a stable UV-resistant silk is formed through chemical grafting and nanocomposite anti-ultraviolet liquid impregnation, combining with a flexible crosslinking network to reduce production costs.
It achieves improved UV resistance and durability, maintains the softness of the fiber, reduces production costs, and is suitable for high-end outdoor clothing and medical dressings.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, in particular to anti-ultraviolet silk and a preparation method thereof. Background Art
[0002] Ordinary silk fabrics are susceptible to photodegradation under ultraviolet radiation, resulting in a decrease in mechanical properties (such as fiber microcrystallization and hydrogen bond breakage). Existing technologies, while inorganic nanoparticles (such as TiO2 and ZnO) can improve UV resistance, suffer from weak fiber bonding and easy shedding. Currently, the following methods are primarily used to improve UV resistance: 1. Inorganic nanoparticles (such as TiO2, ZnO): Although they can improve UV resistance, they have problems such as weak binding force and easy shedding. In addition, nanoparticles may reduce the softness and breathability of silk. 2. Chemical modification: For example, patent CN109736082B discloses a super-hydrophobic, UV-resistant, flame-retardant silk fabric and its preparation method, which uses laccase-catalyzed oxidation of polyphenol grafting. However, this requires an acidic environment (pH 4-5) and oxygen supply, making the process complex and costly. Although Xiangyunsha achieves UV resistance through the yam dyeing and finishing process, it relies on traditional processes, making industrialization difficult.
[0003] 3. Multi-layer composite structure: For example, protection is achieved by superimposing UV protection layers and heat insulation layers, but the structure is complex and affects the natural texture of silk.
[0004] Therefore, in view of the common problems of poor durability, complex process or functional sacrifice in existing technologies, there is an urgent need to develop a silk preparation method that combines chemical grafting and physical composite technology, so as to achieve the preparation of UV-resistant silk with stable loading of UV absorbers and long-term protection by optimizing the nanoparticle dispersion and cross-linking process. Summary of the Invention
[0005] In view of this, in order to overcome the shortcomings of the existing technology, the purpose of the present invention is to provide an anti-ultraviolet silk and a preparation method thereof, which achieves a synergistic improvement in anti-ultraviolet performance, durability and mechanical properties through nano-composite and chemical grafting technology. It is suitable for the field of high value-added textiles and fills the defects of easy shedding of nanoparticles and complex processes in traditional technologies.
[0006] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides an anti-ultraviolet silk, which is prepared by chemically grafting degummed mulberry silk and impregnating and curing it with a nano-composite anti-ultraviolet liquid, wherein the anti-ultraviolet liquid contains a phenolic hydroxyl conjugate, an aldehyde cross-linking agent and modified nanoparticles.
[0007] As a further embodiment of the present invention, the phenolic hydroxyl group-containing conjugate is a compound of baicalein, ferulic acid and honeysuckle polyphenols in a mass ratio of 1:1:3 and a total concentration of 0.5-2 wt%.
[0008] As a further embodiment of the present invention, the aldehyde cross-linking agent is formaldehyde, vanillin or cinnamaldehyde, and the molar amount of the aldehyde cross-linking agent is 0.9-4 times that of the phenolic hydroxyl group-containing conjugate.
[0009] As a further solution of the present invention, the modified nanoparticles are nano-ZnO or TiO2, the particle size of the modified nanoparticles is 20-50nm, the concentration is 1-3wt%, and the nano-ZnO or TiO2 is surface grafted after modification with a silane coupling agent KH550, thereby solving the problem of easy shedding of traditional inorganic particles and improving the interface bonding strength with silk fibers.
[0010] As a further embodiment of the present invention, the solvent of the anti-ultraviolet liquid is a mixture of ethanol and water, with a volume ratio of 1:3-5 and a pH of 6.5-7.5.
[0011] In a second aspect, the present invention further provides a method for preparing UV-resistant silk, comprising the following steps: a pretreatment: The degummed silk was immersed in a DMF solution containing 5-10wt% tert-butyl acetate, reacted at 80-150 ° C for 1-6 hours, washed and dried to obtain pretreated silk; b. Preparation of anti-UV liquid: The phenolic hydroxyl conjugate, aldehyde crosslinking agent and modified nano ZnO / TiO2 are dispersed in an ethanol / water solvent to prepare an anti-UV liquid; c. Impregnation: Immerse the pretreated silk in an anti-UV solution at 40-60°C with ultrasonic assistance for 2-6 hours; d. Curing: The impregnated silk is rolled (liquid content 60-90%), pre-dried at 80-100°C for 10-30 minutes, and heat-cured at 120-160°C for 20-60 minutes to obtain UV-resistant silk.
[0012] As a further embodiment of the present invention, the pretreatment solution in step a further comprises 1-3 wt% sodium carbonate solution, and the pretreatment is carried out at 80-100° C. for 20-40 minutes to remove residual sericin.
[0013] As a further solution of the present invention, the nano ZnO is prepared by an in-situ generation technology, including immersion in zinc nitrate solution, followed by alkaline reaction and high-temperature treatment.
[0014] As a further solution of the present invention, the ultrasonic frequency is 20-50kHz and the power is 200-500W.
[0015] As a further solution of the present invention, after heat curing, the unbound components are removed by washing with water, and polyethylene glycol diglycidyl ether is used as an auxiliary cross-linking agent with a concentration of 0.5-1.5 wt%.
[0016] Compared with the prior art, the present invention provides an anti-ultraviolet silk and a preparation method thereof, which has the following beneficial effects: When preparing the anti-ultraviolet silk of the present invention, nano ZnO or TiO2 is used to reflect / scatter ultraviolet rays, and phenolic hydroxyl conjugates are used to absorb ultraviolet energy and convert it into heat energy for dual protection, so that the prepared anti-ultraviolet silk has high-efficiency anti-ultraviolet performance; the fiber crystallinity is enhanced by acetylation modification, stress concentration is reduced by a nano-composite layer, and a flexible cross-linking network of aldehyde cross-linking agents and polyethylene glycol diglycidyl ether is used to avoid fiber hardening caused by traditional inorganic coatings, thereby retaining the softness of the silk; the low-temperature reaction conditions are milder, and an ethanol / water solvent system and natural plant extracts are used to replace precious metal raw materials, thereby reducing production costs. The silk is suitable for high-end outdoor clothing, medical dressings and smart textiles, and has significant market potential. DETAILED DESCRIPTION
[0017] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the specification.
[0018] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0019] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.
[0020] Example 1 The first embodiment of the present invention provides an anti-ultraviolet silk, and the specific preparation steps of the anti-ultraviolet silk are as follows: 1. Raw materials and components.
[0021] (1) Silk substrate: degummed mulberry silk fabric (pretreated with sodium carbonate).
[0022] (2) Anti-UV liquid formula: Conjugate containing phenolic hydroxyl groups: baicalein and ferulic acid: honeysuckle polyphenols are compounded in a mass ratio of 1:1:3, with a total concentration of 1.2wt%; Aldehyde cross-linker: vanillin (molar amount is twice that of the conjugate); Modified nanoparticles: nano-TiO2 (particle size 30nm, concentration 2wt%), modified with silane coupling agent KH550; Auxiliary cross-linking agent: polyethylene glycol diglycidyl ether (concentration 1.0wt%); Solvent: A mixture of ethanol and water (volume ratio 1:4, pH 7.0).
[0023] 2. Preparation steps.
[0024] Step 1: Silk Pretreatment: Degumming treatment: The degummed mulberry silk was immersed in 2wt% sodium carbonate solution and treated at 90℃ for 30 minutes to remove residual sericin, washed with water until neutral and dried.
[0025] Acetylation modification: The degummed silk was immersed in a DMF solution containing 8 wt% tert-butyl acetate (bath ratio 1:10) and reacted at 120 °C for 4 h to graft acetoacetate groups, followed by rinsing with ethanol three times and drying.
[0026] Step 2: Preparation of anti-UV liquid: Nano-TiO2 modification: Nano-TiO2 and silane coupling agent KH550 (added amount is 3% of TiO2 mass) are ultrasonically dispersed in ethanol for 30 minutes to form a stable suspension; Mixing and dispersion: add baicalein, ferulic acid, honeysuckle polyphenols, vanillin and modified nano-TiO2 into ethanol / water solvent and stir magnetically for 2 hours to form a uniform anti-UV liquid.
[0027] Step 3: Ultrasonic assisted impregnation: The pretreated silk was immersed in anti-UV liquid and immersed at 50 °C and 30 kHz ultrasonic wave (power 300 W) for 4 h to ensure that the nanoparticles and conjugates fully penetrated into the fiber.
[0028] Step 4: Curing and post-processing.
[0029] Rolling: liquid rate is controlled at 80%; Pre-baking: 90℃ for 20 minutes; Thermal curing: 150℃ for 40 minutes; Washing: Wash with deionized water to remove unbound components, and dry at room temperature to obtain UV-resistant silk.
[0030] The UV resistance performance of the UV-resistant silk prepared in this example was tested (according to GB / T 18830-2009), and the obtained UPF value was: 55 (initial) → 50 (after 50 washes, the retention rate was ≥90%); UVA transmittance: 4.5%; UVB transmittance: 0.8%.
[0031] Mechanical property testing of the UV-resistant silk produced in this example showed an increase in tensile strength from 3.6 cN / dtex to 4.3 cN / dtex (a 19% increase), and a dense composite layer approximately 120 nm thick formed on the fiber surface. Durability was demonstrated by covalent bonding of nano-TiO2 to the fiber via a silane coupling agent, with a shedding rate of less than 5% after washing (ICP-OMS analysis). The ethanol / water solvent system reduces the use of organic solvents, with plant extracts comprising ≥35% of the total content, meeting OEKO-TEX® environmental standards.
[0032] In the UV-resistant silk prepared in this embodiment, baicalein and ferulic acid are covalently bonded to the silk amino groups through the Mannich reaction to form a molecular-level UV absorption layer; nano-TiO2 is modified with silane to enhance interfacial bonding and reflect / scatter UV rays; the silane coupling agent KH550 solves the problem of easy shedding of traditional nanoparticles; low-temperature pre-drying reduces fiber damage, and high-temperature curing enhances the stability of the cross-linked network. The resulting UV-resistant silk is suitable for medical dressings (antibacterial and UV-resistant synergistic effects) and outdoor sportswear (excellent washability).
[0033] Example 2 The second embodiment of the present invention provides an anti-ultraviolet silk, and the specific preparation steps of the anti-ultraviolet silk are as follows: 1. Raw materials and components.
[0034] (1) Silk substrate: degummed mulberry silk fabric (width 100 cm, weight 40 g / m²).
[0035] (2) Anti-UV liquid formula: Conjugate containing phenolic hydroxyl groups: baicalein: ferulic acid: honeysuckle polyphenols = 1:1:3 (total concentration 1.5 wt%); Aldehyde cross-linker: vanillin (molar amount is twice that of the conjugate); Modified nanoparticles: nano-ZnO (particle size 30 nm, concentration 2 wt%), modified with silane coupling agent KH550 (addition amount is 3% of ZnO mass); Auxiliary cross-linking agent: polyethylene glycol diglycidyl ether (PEGDE, concentration 1.0 wt%); Solvent: A mixture of ethanol and water (volume ratio 1:4, pH 7.0).
[0036] 2. Preparation steps.
[0037] Step 1: Silk Pretreatment: The degummed mulberry silk was immersed in 2.5 wt% sodium carbonate solution and treated at 90 °C for 30 min to remove residual sericin, washed with water until neutral and dried.
[0038] Acetylation modification: The degummed silk was immersed in a DMF solution containing 7 wt% tert-butyl acetate (bath ratio 1:10) and reacted at 120 °C for 4 h to graft acetoacetate groups, followed by rinsing with ethanol three times and drying.
[0039] Step 2: Preparation of anti-UV liquid: Nano-ZnO modification: Nano-ZnO and silane coupling agent KH550 were ultrasonically dispersed in ethanol (30 kHz, 30 min) to form a stable suspension.
[0040] Mixing and dispersion: Add baicalein, ferulic acid, vanillin, PEGDE and modified nano ZnO into ethanol / water solvent and stir magnetically for 2 hours to form a uniform anti-UV solution. Step 3: Ultrasonic assisted impregnation: The pretreated silk was immersed in anti-UV solution and immersed at 50 °C and 30 kHz ultrasonic wave (power 300 W) for 4 h to ensure that the nanoparticles and conjugates penetrated deep into the fiber.
[0041] Step 4: Curing and post-processing: Rolling: liquid rate is controlled at 85%; Pre-baking: 90℃ for 20 minutes; Thermal curing: 140℃ for 40 minutes; Washing: Wash with deionized water to remove unbound components, and dry at room temperature to obtain UV-resistant silk.
[0042] The UV-resistant silk prepared in this example was tested for UV resistance (according to GB / T 18830-2009). The UPF value was 58 (initial) → 53 (retention rate ≥ 91% after 50 washes according to GB / T 3921-2008). UVA transmittance was 4.2%, and UVB transmittance was 0.7%. Mechanical properties testing of the UV-resistant silk prepared in this example showed an increase in tensile strength from 3.5 cN / dtex to 4.13 cN / dtex (an increase of 18%). A dense composite layer with a thickness of approximately 150 nm was formed on the fiber surface. Nano-ZnO was covalently bonded to the fiber via a silane coupling agent, with a post-wash shedding rate of less than 5% (ICP-OMS analysis). The ethanol / water solvent system reduces the amount of organic solvents used, and the plant extract content is ≥ 35%, meeting OEKO-TEX® standards.
[0043] The anti-ultraviolet silk prepared in this embodiment is covalently bonded to the silk amino groups through the Mannich reaction of baicalein and ferulic acid to form a molecular-level ultraviolet absorption layer; nano-ZnO is modified by silane to enhance interfacial bonding and reflect / scatter ultraviolet rays; after zinc nitrate impregnation, the pH is adjusted to 9.5 with ammonia water, and the reaction is carried out at 80°C for 2 hours to generate a Zn(OH)2 precursor, which is thermally decomposed at 140°C to form uniform ZnO particles; low-temperature pre-drying reduces fiber yellowing, and high-temperature curing enhances the stability of the cross-linked network, and vanillin is used to replace formaldehyde to reduce toxicity; plant extracts and nano-ZnO are compounded to reduce dependence on heavy metals.
[0044] Example 3 The third embodiment of the present invention provides an anti-ultraviolet silk. The specific preparation steps of the anti-ultraviolet silk are as follows: 1. Raw materials and components.
[0045] (1) Silk substrate: degummed mulberry silk fabric (weight 45 g / m², width 110 cm).
[0046] (2) Anti-UV liquid formula: Conjugate containing phenolic hydroxyl groups: baicalein: ferulic acid: honeysuckle polyphenols = 1:1:3 (total concentration 1.8 wt%); Aldehyde cross-linking agent: cinnamaldehyde (molar amount is 3 times that of the conjugate); Modified nanoparticles: nano-ZnO (particle size 25 nm, concentration 2.5 wt%), modified with silane coupling agent KH550 (addition amount is 4% of ZnO mass); Auxiliary cross-linking agent: polyethylene glycol diglycidyl ether (PEGDE, concentration 1.2 wt%); Solvent: A mixture of ethanol and water (volume ratio 1:4, pH 7.0).
[0047] 2. Preparation steps.
[0048] Step 1: Silk Pretreatment: Degumming treatment: The degummed mulberry silk was immersed in a 3 wt% sodium carbonate solution at 95°C for 35 minutes to completely remove the residual sericin, then washed with water until neutral and dried; Acetylation modification: The degummed silk was immersed in a DMF solution containing 9 wt% tert-butyl acetate (bath ratio 1:10) and reacted at 120 °C for 5 h to graft acetoacetate groups to enhance the reaction activity. The silk was then rinsed with ethanol three times and dried.
[0049] Step 2: Preparation of anti-UV liquid: (1) In-situ generation of nano ZnO: The silk was immersed in 0.1 M zinc nitrate solution at room temperature for 30 minutes; After immersion, the sample was taken out and reacted in ammonia water (pH 9.5) for 2 h to generate Zn(OH)2 precursor; The ZnO nanoparticles were uniformly dispersed after high temperature treatment at 140°C for 40 minutes.
[0050] (2) Surface modification: The in situ generated nano-ZnO and the silane coupling agent KH550 (ethanol dispersion system) were ultrasonically treated (30 kHz, 40 minutes) to form a stable suspension.
[0051] (3) Mixing and dispersion: Add baicalein, ferulic acid, honeysuckle polyphenols, cinnamaldehyde and PEGDE into ethanol / water solvent and stir magnetically for 3 hours until uniform.
[0052] Step 3: Ultrasonic assisted impregnation: The pretreated silk was immersed in anti-UV solution and immersed at 55 °C and 30 kHz ultrasonic wave (power 350 W) for 5 h to ensure that the nanoparticles and conjugates penetrated deep into the fiber.
[0053] Step 4: Curing and post-processing: Rolling: liquid rate is controlled at 85%; Pre-baking: 90℃ for 20 minutes; Thermal curing: 145℃ for 35 minutes; Water washing: Wash with deionized water to remove unbound components and dry at room temperature.
[0054] The UV-resistant silk prepared in this example was tested for UV resistance (according to GB / T 18830-2009). The results showed a UPF value of 60 (initial) → 55 (retention rate ≥ 92% after 50 washes according to GB / T 3921-2008). UVA transmittance was 3.8%, and UVB transmittance was 0.5%. Mechanical properties testing of the UV-resistant silk prepared in this example showed an increase in tensile strength from 3.4 cN / dtex to 4.2 cN / dtex (a 23.5% increase). A dense composite layer with a thickness of approximately 180 nm was formed on the fiber surface. Nano-ZnO was covalently bonded to the fiber via a silane coupling agent, with a post-wash shedding rate of less than 4% (ICP-OMS analysis). The ethanol / water solvent system reduces the amount of organic solvents used, and the plant extract content is ≥ 40%, meeting OEKO-TEX® standards.
[0055] The UV-resistant silk prepared in this example forms a molecular-level UV absorption layer through the Mannich reaction of a baicalein-ferulic acid-honeysuckle polyphenol composite system, while also providing antioxidant function. In situ generated nano-ZnO is combined with silane modification to improve particle dispersibility and bonding strength, solving the problem of easy shedding of traditional inorganic particles. Gradient temperature curing (pre-baking at 90°C → thermal curing at 145°C) balances fiber protection and cross-linking efficiency to avoid yellowing or embrittlement. Ultrasonic-assisted impregnation (30kHz) enhances penetration depth and ensures uniform distribution of nanoparticles inside and outside the fiber. Cinnamaldehyde is used instead of formaldehyde to reduce toxicity. The combination of plant extracts and nano-ZnO reduces dependence on heavy metals.
[0056] Therefore, when preparing the anti-ultraviolet silk of the present invention, nano ZnO or TiO2 is used to reflect / scatter ultraviolet rays, and phenolic hydroxyl conjugates are used to absorb ultraviolet energy and convert it into heat energy for dual protection, so that the prepared anti-ultraviolet silk has high-efficiency anti-ultraviolet performance; the fiber crystallinity is enhanced by acetylation modification, stress concentration is reduced by the nano-composite layer, and the flexible cross-linking network of aldehyde cross-linking agent and polyethylene glycol diglycidyl ether is used to avoid fiber hardening caused by traditional inorganic coatings, thereby retaining the softness of silk, and the low-temperature reaction conditions are milder. The ethanol / water solvent system and natural plant extracts are used to replace precious metal raw materials, thereby reducing production costs. The silk is suitable for high-end outdoor clothing, medical dressings and smart textiles, and has significant market potential.
[0057] It is important to note that the construction and arrangement of the present application, as illustrated in various exemplary embodiments, are illustrative only. Although only a few embodiments are described in detail in this disclosure, those reading this disclosure will readily appreciate that numerous modifications are possible (e.g., variations in the size, dimensions, structure, shape, and proportions of various components, as well as parameter values (e.g., temperature, pressure, etc.), mounting arrangements, use of materials, color, orientation, etc.) without materially departing from the novel teachings and advantages of the subject matter described herein. For example, components shown as integrally formed may be constructed from multiple parts or components, the positions of components may be inverted or otherwise altered, and the nature, number, or position of discrete components may be modified or changed. All such modifications are therefore intended to be encompassed within the scope of this invention. The order or sequence of any process or method steps may be altered or resequenced according to alternative embodiments. In the claims, any "means-plus-function" clause is intended to cover structures described herein that perform the recited function, and not only structural equivalents but also equivalent structures. Other substitutions, modifications, changes, and omissions may be made in the design, operating conditions, and arrangement of the exemplary embodiments without departing from the scope of this invention. Therefore, the invention is not limited to the specific embodiments, but extends to various modifications that still fall within the scope of the appended claims.
[0058] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment may not be described (i.e., those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention).
[0059] It will be appreciated that in the development of any actual embodiment, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will, for those of ordinary skill having the benefit of this disclosure, be a routine undertaking of design, fabrication, and production without undue experimentation.
[0060] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An anti-ultraviolet silk, characterized in that: The anti-ultraviolet material is prepared by chemical grafting of degummed mulberry silk, impregnation with nano-composite anti-ultraviolet liquid and curing. The anti-ultraviolet liquid contains phenolic hydroxyl conjugates, aldehyde cross-linking agents and modified nano-particles.
2. The anti-ultraviolet silk according to claim 1, characterized in that: The phenolic hydroxyl group-containing conjugate is prepared by compounding baicalein, ferulic acid and honeysuckle polyphenols in a mass ratio of 1:1:3 and a total concentration of 0.5-2 wt %.
3. The anti-ultraviolet silk according to claim 2, characterized in that: The aldehyde cross-linking agent is formaldehyde, vanillin or cinnamaldehyde, and the molar amount of the aldehyde cross-linking agent is 0.9-4 times that of the phenolic hydroxyl conjugate.
4. The anti-ultraviolet silk according to claim 3, characterized in that: The modified nanoparticles are nano ZnO or TiO2, the particle size of the modified nanoparticles is 20-50nm, the concentration is 1-3wt%, and the nano ZnO or TiO2 is surface grafted after being modified with a silane coupling agent KH550, thereby solving the problem of easy shedding of traditional inorganic particles and improving the interface bonding strength with silk fibers.
5. The anti-ultraviolet silk according to claim 4, characterized in that: The solvent of the anti-ultraviolet liquid is a mixture of ethanol and water with a volume ratio of 1:3-5 and a pH of 6.5-7.
5.
6. A method for preparing the UV-resistant silk according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: a pretreatment: The degummed silk was immersed in a DMF solution containing 5-10wt% tert-butyl acetate, reacted at 80-150 ° C for 1-6 hours, washed and dried to obtain pretreated silk; b. Preparation of anti-UV liquid: The phenolic hydroxyl conjugate, aldehyde crosslinking agent and modified nano ZnO / TiO2 are dispersed in an ethanol / water solvent to prepare an anti-UV liquid; c. Impregnation: Immerse the pretreated silk in an anti-UV solution at 40-60°C with ultrasonic assistance for 2-6 hours; d. Curing: The impregnated silk is rolled, pre-dried at 80-100°C for 10-30 minutes, and heat-cured at 120-160°C for 20-60 minutes to obtain UV-resistant silk.
7. The method for preparing the UV-resistant silk according to claim 6, wherein: The pretreatment solution in step a further comprises 1-3 wt% sodium carbonate solution, which is treated at 80-100° C. for 20-40 minutes to remove residual sericin.
8. The method for preparing the UV-resistant silk according to claim 7, wherein: The nano ZnO is prepared by an in-situ generation technology, including immersion in a zinc nitrate solution, followed by alkaline reaction and high-temperature treatment.
9. The method for preparing the UV-resistant silk according to claim 6, wherein: The ultrasonic frequency is 20-50kHz and the power is 200-500W.
10. The method for preparing the UV-resistant silk according to claim 9, characterized in that: After thermal curing, the unbound components are removed by water washing, and polyethylene glycol diglycidyl ether is used as an auxiliary cross-linking agent with a concentration of 0.5-1.5wt%.
Citation Information
Patent Citations
A superhydrophobic, UV-resistant, flame-retardant silk fabric and its preparation method
CN109736082B
Anti-ultraviolet ray silk fabric production method
CN103469543A
Silk finishing liquid and treatment method adopting silk finishing liquid
CN116676784A
Anti-ultraviolet silk and preparation method thereof
CN118621578A